Developmental Dyscalculia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
An 11-year-old, Hebrew speaking boy of normal intelligence, referred to Alyn Hospital, and Schneider Children's Medical Center, Jerusalem, for evaluation of learning and attentional problems, was found to have a profound dyscalculia based on a proposed lack of "cardinal/ordinal skills acquisition device" (COSAD).